Ліквідація товариства «Просвіта» на західноволинських землях (1928-1932 рр.) : причини та наслідки - Крамар, Юрій Вікторович; Kramar, Yurii V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті висвітлюються причини ліквідації польською владою культурно-освітнього товариства «Просвіта» на території Волинського воєводства наприкінці 1920 – початку 1930-х рр. Показано наслідки, яка мала ця подія на суспільно-політичні та культурні процеси в краї.

This article studies the cultural and educational activity of the society «Prosvita» on the territory of the Volyn region in 1920–1930-s. We show that Prosvita became one of the main centers of ukrainian national and cultural movement in the Volyn region during the interwar period. The regeneration of the Ukrainian folk choreography traditions, the development of the instrumental folk music and professional theatre on the Western Volyn lands were connected with that organization.The society took care of the ukrainian schooling and it had developed different forms of out-of-school education among local Ukrainians. Another aspect of this research is the character of the relation between Polish administration and local Ukrainian community. We come to a conclusion that the main goal of the Poland's state policy concerning Ukrainian population in Volyn was step by step elimination of any organizational forms of Ukrainian cultural and educational life in the region and a gradual denationalization of the Ukrainians.
The liquidation of «Prosvita» organization on the Western Volyn lands in the years 1928–1932: causes and consequences
Keywords: Просвіта; «Prosvita»; Волинське воєводство; Volyn region; українська громада; the Ukrainian community; національний рух; national movement; польська адміністрація; Polish administration